RANCANG BANGUN SISTEM INFORMASI EVENT ORGANIZER BERBASIS WEB PADA PT. DANADIPA NUSA ARTA JAKARTA - Widiarti Lestariningsih; Teguh Murianto (JURNAL LENTERA ICT, 2023)
This research was motivated by observations at PT. Danadipa Nusa Arta. The event management process at the company is still carried out manually, which causes obstacles in data processing, such as creating event activities and inputting guest data, errors in writing names or titles, differences between invited and uninvited guests, and reports to be used as information as needed. To overcome these problems, this study aims to design an Event Organizer information system. The research problems are the design and development of an event management system to help event organizers speed up their work, help receptionists distinguish between invited and uninvited guests, and help clients receive attendance reports.